Optimalisasi Jaminan Produk Halal: Studi Implementasi UU No. 33 Tahun 2014 pada Usaha Depot Air Minum Isi Ulang di Watang Sawitto - Rubiyanto, Fitri Anggraini Ningrum (SIGHAT: JURNAL HUKUM EKONOMI SYARIAH, 2024)
Law Number 33 of 2014 requires mass-produced products to be halal certified. Filled drinking water products in Pinrang Regency do not have adequate halal permits and labeling. Apart from that, there is still very little attention paid to the cleanliness of the gallons. Law Number 33 of 2014 concerning Halal Product Guarantees is a consideration in determining the quality of drinking water as a halalization standard. Therefore, this research aims to determine the extent of the implementation of Law Number 33 of 2014 concerning Halal Product Guarantees for refill drinking water depot businesses regarding the halal certification of their drinking water depots.The research method used in this thesis is a qualitative descriptive research method with a case study approach (field research), the data in this research was obtained from primary and secondary data. Data collection techniques are obtained from observation, interview results, and documentation.The results of this research show that: 1) The implementation of the Halal Product Guarantee Law in Pinrang Regency as a whole is not optimal because the Ministry of Religion as an institution given authority by the central government is only limited to supervision because enforcing regulations is the full authority of the central government; 2) Enforcement of regulations for business actors is still not optimal regarding sanctions for violations of placing unofficial labels on their business products; 3) The impact on the level of consumer confidence is reduced as well as the quality of production of refill drinking water which has an impact on consumers' health which is their right to be protected, especially regarding food or drink consumption.